Studi Paradigma: Integrasi Pengetahuan UIN Maulana Malik Ibrahim Malang dan UIN Sunan Gunung Djati Bandung - Mohamad Yudiyanto; Tatang Muh Nasir; Rahmat; Ali Imron; Erni Haryanti (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
Technological developments, especially artificial intelligence (AI), have encouraged innovation in various fields, including education. This research aims to explore the application of deep learning in the learning process to increase the effectiveness and efficiency of education. Using a qualitative method based on literature studies, data is collected from relevant journals, articles, and books. The results show that deep learning, as a branch of AI, is able to overcome various complex problems, such as pattern analysis, learning personalization, and adaptive evaluation. The system utilizes a layered artificial neural network that mimics the work of the human brain to generate accurate predictions and intelligent solutions. In the context of Islamic education, the application of this technology can support the development of student competencies holistically, in line with religious values. The conclusion of this study confirms that the integration of deep learning in education not only improves the quality of learning, but also prepares students to face the challenges of the digital era.